Implantasi hibrid alat terapi resinkronisasi jantung - Alexander Edo Tondas; Yoga Yuniadi (The Indonesian Heart Association, 2010)
Recent trials have proven the clinical and functional benefits of cardiac resynchronization therapy (CRT) by biventricular pacing in patients (pts) with severe heart failure and intraventricular conduction delay, principally left bundle branch block (LBBB). However, placement of the transvenous left ventricular lead of CRT device is unsuccessful in 5–10% of patients and a further 20% fail to respond. For these groups, epicardial left ventricular lead placement is one alternative A 75-year-old male patient diagnosed as non ischemic dilated cardiomyopa-thy patient NYHA Class III-IV meeting the clinical initiation criteria of QRS duration > 120 msec, and low ejection fraction (=35%), with worsening symptoms despite one year of medical therapy.A hybrid approach of LV lead implantation by mini thoracostomy and conventional implantation of the RA and RV leads were performed because the coronary sinus cannot be accessed transvenously due to small caliber even after angioplasty. The patient responded quite well to CRT and was discharged with stable he-modynamics, and NYHA Functional Class II.